Comparative studies of various fuel reforming methods - Mirasu Ayyasamy Vimalraj. (2010)
The production of energy without polluting our atmosphere is one of the key challenges faced by our generation. Fuel cell, is one of the promising technology to produce clean energy to our future, needs clean hydrogen and air as their feed. Finding out optimum condition for the production of hydrogen from various fuels is one of the primary investigations of fuel reforming laboratory ofNanyang Technological University (NTU).